Mast cell activation markers for in vitro study. Issue 4 (3rd July 2020) - Sahid, Muhammad Novrizal Abdi; Kiyoi, Takeshi
ABSTRACT: Mast cells (MCs) are well known for their role in allergic conditions. This cell can be activated by various types of secretagogues, ranging from a small chemical to a huge protein. Mast cell activation by secretagogues triggers the increase in intracellular calcium (iCa 2+ ) concentration, granule trafficking, and exocytosis. Activated mast cells release their intra-granular pre-stored mediator or the newly synthesized mediator in the exocytosis process, in the form of degranulation or secretion. There are at least three types of exocytosis in mast cells, which are suggested to contribute to the release of different mediators, i.e., , piecemeal, kiss-and-run, and compound exocytosis. The status of mast cells, i.e., activated or resting, is often determined by measuring the concentration of the released mediator such as histamine or β-hexosaminidase. This review summarizes several mast cell components that have been and are generally used as mast cell activation indicator, from the classical histamine and β-hexosaminidase measurement, to eicosanoid and granule trafficking observation. Basic principle of the component determination is also explained with their specified research application and purpose. The information will help to predict the experiment results with a certain study design.